CCNP Voice - Wallace, Kevin; Safari eBooks ([Indianapolis, Ind.] : Pearson Certification, 2012)
"CCNP Voice LiveLessons is a collection of 72 video training sessions targeting a selection of topics in the CVOICE, CIPT1, CIPT2, TVOICE, and CAPPS curriculum."--Resource description page (view 22 June 2012).
Presenter: Kevin Wallace.
Keywords: Computer networks; Virtual LANs; Routers (Computer networks); Electronic books